THE FAMILY’S PROBLEM AND TEENAGER IN CONFLICT WITH THE LAW: POINTS AND COUNTERPOINTS - Vanisse Monteiro Campos; Gisele Silva Lira de Resende (Revista Eletrônica do Curso de Direito da UFSM, 2016)
The discussion about teenagers who engage in violent actions have been considered a large social problem, whether as victims or as perpetrators. In this context, this research, carried out in the area of Human Rights aims higher, understand which elements of the family dynamic of adolescents in conflict with the law, which are a measure of deprivation of liberty, in the Socio-Educational System, the municipality of Barra do Garças-MT, contributed to these enter in the world of infraction. This is an exploratory research, qualitative approach, which analyses, so narrow, the family dynamics of these interns. It was used in theoretical discussion, works of Kozen, Dias, Tepedino, Statute of children and adolescents, among others. Already the field research was carried out in the aforementioned institution. It is concluded that the home environment can influence the teenager to commit unlawful acts.